Primary Extranodal Marginal Cell Lymphoma, MALT Type, of the Endometrium Arising in a Patient With Rheumatoid Arthritis: Report of a Case. (July 2016) - Magnoli, Francesca; Cimetti, Laura; Bernasconi, Barbara; Sahnane, Nora; Redaelli, Isabella; Riva, Cristina; Uccella, Silvia
Abstract : Primary marginal zone B-cell MALT-type lymphomas of the uterine corpus are exceedingly rare entities, with only 6 cases reported in the literature to date. We present the additional case of a 70-yr-old white woman who underwent a laparoscopic total hysterectomy with bilateral salpingo-oophorectomy for an asymptomatic ovarian cyst. At microscopic examination, endometrial samples showed a dense, nodular lymphocytic infiltrate, suggestive of a lymphoproliferative disorder. Morphology, immunohistochemistry, and molecular analysis supported the diagnosis of MALT-type lymphoma of the endometrium. Benign reactive conditions, such as endometritis and other small B-cell lymphomas were ruled out. Moreover, we investigated the pathogenesis of our case, focusing on Chlamydia trachomatis infection, chromosomal translocations affecting the NF-kB pathway, and discussing the role of autoimmunity in the development of MALT-type lymphomas.